PENGARUH TUKUL ARWANA SEBAGAI CELEBRITY ENDORSER TERHADAP BRAND AWARENESS MASYARAKAT (STUDI KASUS IKLAN XL VERSI TUKUL ARWANA) - muhammad khoiruman (KELOLA, 2015)
Considerations to be made by marketers in selecting endoser a product other products form the basis of this study. This study aims to determine the effect attributes (performance) endorser of the brand awareness Tukul Arwana in advertising XL. This research is a survey with a sample of the overall amount to 120 respondents. The sampling technique used was purposive sampling. Data collection instruments such as questionnaires and analysis tools used multiple linear regression. Based on the results of this study concluded that there was a significant relationship between dimensions Credibility Celebrity, Celebrity and Celebrity Suitability Attractivenes simultaneously to Brand awareness of society who view the ads of XK in Tukul Arwana version. Celebrity dimensil Credibility has the greatest influence on the brand awareness of society. Keywords: Credibility Celebrity, Celebrity and Celebrity Attractivenes Suitability and Brand awareness